ANALISIS DAN PERFORMA WEBSITE WEBSITE PEMERINTAH PROVINSI JAWA TENGAH MENGGUNAKAN METODE AUTOMATED USABILITY TESTING - irawan, sandy (JTRISTE, 2023)
The Government of Central Java Province is committed to providing information and services to the public through its digital platform, the jatengprov.go.id website. This website is designed to make it easier for the public to access information about policies, programmes, and services offered by the provincial government. However, this website is experiencing some significant performance issues while trying to provide the best digital service. Some problems with the speed and efficiency of websites were found through tests conducted using Google PageSpeed Insights and GTmetrix. The website jatengprov.go.id received a score of 61, placing it in the middle category, according to a Google PageSpeed Insights desktop version test. However, the score dropped drastically on the mobile version, with a score of only 48, indicating poor performance on mobile devices. Although this website received a high score for SEO with a rating of 100, which indicates that it has been optimized for search engines, accessibility elements and best practices each received a score of 70 and 56. As a result of GTmetrix analysis, the website jatengprov.go.id received a "D" score with a performance score of 63% and a structural score of 62%. According to Web Vitals, Largest Contentful Paint (LCP) lasted 3.1 seconds, longer than recommended. However, the Total Blocking Time (TBT) and Cumulative Layout Shift (CLS) values are excellent, 0.0, respectively. This suggests that, although the page does not undergo much layout changes during loading, the time it takes to display the most important components still needs to be fixed. With this change, the website jatengprov.go.id is expected to improve the user experience and support the goal of the Government of Central Java Province to provide effective and efficient digital services to the public. Regularly tracking and improving website performance using tools like Google PageSpeed Insights and GTmetrix is vital.